A New Parameter of Hip Instability in Developmental Dysplasia of the Hip (DDH): Teardrop Distance - Yang, Guoyue; Zhang, Zhendong; Hou, Xiaobin; Luo, Dianzhong; Cheng, Hui; Xiao, Kai; Liu, Hui; Zhang, Hong (Frontiers in Surgery, 2022)
Background: Hip instability is one of the etiologies of accelerated onset of osteoarthritis in developmental dysplasia of the hip (DDH). There are some radiological parameters for hip instability in hip dysplasia like broken shenton’s line, elevated acetabular index, reduced lateral center edge angle (LCEA), upsloping lateral sourcil. We have discovered a new index of teardrop distance (TD) for assessing instability.Herein, we hypothesized that increased TD could be used as evidence of hip instability in DDH patients, which we verified using TD as an auxiliary diagnostic parameter for DDH, from supine to standing position. Methods: Female DDH patients undergoing Bernese periacetabular osteotomy (PAO) were enrolled in the DDH group, and normal female volunteers were in the control group. Anteroposterior radiographs of the pelvis in the supine and standing positions were taken, and LCEA, Tönnis angle (TA), sharp angle (SA), and TD were tested using Stata software to analyze the changes between supine and standing anteroposterior pelvic radiographs. Results: There were 26 female volunteers with 52 hips in the control group: supine TD 6.80 ± 0.98 mm, standing TD 6.65 ± 1.3 mm (p > 0.05). A total of 78 patients with 135 hips were included in the DDH group: supine TD 10.51 ± 3.50 mm, standing TD 10.93 ± 4.23 mm (p < 0.05). In either supine or standing position, TD in the DDH group was significantly wider than that in the control group (P < 0.05). In the DDH group, TD was correlated with TA and LCEA (rp 0.494-0.588, P < 0.05); TD was not correlated with SA, weight, or BMI (P > 0.05). There was a weak correlation between TD difference and standing LCEA (rp -0.276, P < 0.05). Conclusion: TD > 10 mm was a common imaging feature of DDH. It increased from supine to standing position, thus indicating hip instability in DDH patients. The hip parameters of both positions should be compared, fully considering the factors of hip stability.